Laser ultrasonic technology for residual stress measurement of 7075 aluminum alloy friction stir welding. (February 2019) - Zhan, Yu; Li, Yingmei; Zhang, Enda; Ge, Yiming; Liu, Changsheng
Highlights: The noncontact laser ultrasonic method is proposed to measure the residual stress in 7075 aluminum alloy FSW. The influence of welding speed and stirring head rotational speed on residual stress is discussed. The new conclusion has been obtained that, when the welding speed is lower, the influence of the rotational speed on the stress is more significant. Abstract: Friction stir welding (FSW) is widely used in the welding of aluminum alloys for aerospace applications, because of its low energy consumption, high efficiency and good mechanical properties. However, the problems of deformation, cracking and fatigue degradation caused by residual stress remain to be solved. In this paper, the residual stress in 7075 aluminum alloy FSW has been measured with laser ultrasonic technology. According to the FSW process and the characteristics of thin plate structure, the residual stress of aluminum alloy sheet is simplified to plane stress state. The pre-stress loading method is proposed and the acoustoelastic constants are obtained. With the known acoustoelastic constants, the longitudinal and transverse FSW residual stresses are measured with the laser ultrasonic. The result shows that the residual stress distribution is obviously asymmetrical and the residual stress on the advancing side is greater than that on the retreating side. The transverse residual stress is smaller than the longitudinal residual stress. Then, the influence of welding speed, rotational speed, tool tilts angle and plunge depth on residual stress is discussed. The results show that the welding speed has great influence on the residual stress, while the influence of the rotational speed on the residual stress is relatively small. When the welding speed is low, the influence of the rotational speed on the stress is more obvious than when the welding speed is higher. For the appropriate range which is determined according to the engineering experience, the effect of tool tilt angle and plunge depth on maximum longitudinal residual stress can be ignored. The research of this paper is of great significance to the application of laser ultrasonic technology in the quality inspection of welded parts and the optimization of FSW process.